1996
DOI: 10.1177/073724779602100302
|View full text |Cite
|
Sign up to set email alerts
|

The Training and Use of Interpreters in Bilingual Psycho-Educational Assessment: an Alternative in Need of Study

Abstract: A multistate survey of 859 school psychologists who indicated prior experience conducting bilingual psycho-educational assessment found that over half had used interpreters. Seventy-seven percent of the school psychologists who reported using interpreters had received no or very little training to do so. Only 37% of the school psychologists reported that their interpreter had received formal training. In only 7% of the cases reported were both school psychologists and interpreters trained in the interpretation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…Only 5% reported that they learned how to use an interpreter during their graduate preparation, and few reported collaborating with interpreters when working, a finding related to their being only “somewhat comfortable” in their use of interpreters. Previous research (Ochoa, Gonzalez, Galarza, & Guillemard, 1996) found that 11% of the school psychologists they sampled were trained in interpreter use, suggesting that explicit attention in how to work with interpreters may be diminishing over time in training programs. On a positive note, many report engaging in recommended practices when working with interpreters by speaking clearly, thoroughly briefing the interpreter, and evaluating his or her native and second language skills.…”
Section: Discussionmentioning
confidence: 98%
“…Only 5% reported that they learned how to use an interpreter during their graduate preparation, and few reported collaborating with interpreters when working, a finding related to their being only “somewhat comfortable” in their use of interpreters. Previous research (Ochoa, Gonzalez, Galarza, & Guillemard, 1996) found that 11% of the school psychologists they sampled were trained in interpreter use, suggesting that explicit attention in how to work with interpreters may be diminishing over time in training programs. On a positive note, many report engaging in recommended practices when working with interpreters by speaking clearly, thoroughly briefing the interpreter, and evaluating his or her native and second language skills.…”
Section: Discussionmentioning
confidence: 98%
“…However, parents are not always offered language interpretation services (Smith et al 2008) and, likely due to concerns about language interpretation quality, some parents may not accept language interpreters provided by education programs (Cheatham, in press;Lopez and Rooney 1997;Ochoa et al 1996). Nonetheless, best practices in early childhood education and early childhood special education include positive educator-family partnerships and communication to ensure meaningful family participation in children's education (Division for Early Childhood 2007; National Association for the Education of Young Children 1995).…”
mentioning
confidence: 98%
“…Unfortunately, the use of ad-hoc translations is a common procedure among school psychologists in the US (about 50% say they have done it; Ochoa, Riccio, Jimenez, de Alba, & Sines, 2004). Compounding the problem is that most school psychologists have not been trained to identify and recruit appropriate translators (Ochoa, Gonzalez, Galarza, & Guillemard, 1996). Inappropriate translators include individuals such as secretaries and janitors (Paone, Malott, & Maddux, 2010), the referred child or older sibling (García-Sánchez, Orellana, & Hopkins, 2011; Tse, 1995), friends of the child or family (Lynch & Hanson, 1996), or foreign-language teachers at the school (Swender, 2003).…”
Section: Step Three: Appropriate Adaptation Proceduresmentioning
confidence: 99%